Gentle blood aspiration and tube cushioning reduce pneumatic tube system interference in lactate dehydrogenase assays. (March 2016) - Strubi-Vuillaume, Isabelle; Carlier, Valentine; Obeuf, Catherine; Vasseur, Francis; Maury, J-Claude; Maboudou, Patrice; Mangalaboyi, Jacques; Durocher, Alain; Launay, David; Noel, Christian; Brousseau, Thierry
Background: Use of a hospital pneumatic tube system may be associated with measurement errors. Methods: A venous blood sample was collected from 79 patients into a pair of lithium heparin tubes; one tube was sent to the laboratory by porter and the other was sent via the pneumatic tube system. Plasma lactate dehydrogenase concentrations were then assayed. Results: Lactate dehydrogenase concentrations were overestimated (median bias: 18.8%) when evacuated vacuum lithium heparin tubes were sent by pneumatic tube system. This bias was reduced by bubble-wrapping the standard lithium heparin tube or using Monovette lithium heparin tubes in aspiration mode (median bias: +8.7% and −0.3%, respectively). Conclusions: Cushioning and aspiration-mode sampling may limit pneumatic tube system-associated overestimation of lactate dehydrogenase concentrations.